A randomised trial of the effect of appearance versus health-framed messages on engagement with an online brief screening and alcohol reduction intervention. Issue 8 (3rd August 2019) - Sallis, Anna; Attwood, Sophie; Harper, Hugo; Larsen, John; Berry, Dan; Vlaev, Ivo; Sanders, Michael; Chadborn, Tim
Abstract: Objectives: To compare the impact of appearance versus health-framed messages on engagement in a brief web-based risk screening and alcohol reduction intervention. Design: Randomised trial delivered via Drinkaware's website. Visitors were exposed to appearance ( n  = 51, 588) or health-framed messages ( n  = 52, 639) directing them towards an AUDIT-C risk screening questionnaire. Users completing this questionnaire were given feedback on their risk level and extended frame-congruent information. Outcomes: The primary outcome is completion of the AUDIT-C questionnaire. The secondary outcome is whether the participant accessed any of four further resources. Results: The appearance-framed message led to a small but significant increase in the number of users completing the AUDIT-C compared to the health-framed message ( n  = 3, 537, 6.86% versus n  = 3, 355, 6.37%, p  < 0.01). Conversely, following subsequent risk feedback, users exposed to extended health-framed information were more likely to access further resources ( n  = 1, 146, 2.17% versus n  = 942, 1.83%, p  < 0.01). Conclusions: Physical appearance-framed messages increased the likelihood of engagement with an online alcohol screening and brief intervention tool, whereas health-framed messages increased the likelihood of accessing further resources. This highlights the potential for the use of multi-level approaches in alcohol reduction interventions.